Selective EMC subunits act as molecular tethers of intracellular organelles exploited during viral entry - Parikshit Bagchi (Nature Portfolio, 2020)
The endoplasmic reticulum membrane protein complex (EMC) is known to play a role in SV40 viral infection but precise mechanisms are unclear. Here, the authors report that the EMC acts as tether of late endosome–endoplasmic reticulum interorganellar membrane contact sites to promote SV40 viral infection.